Awareness & demonstration of fish nutrition promotion programme under APART - Ratha, Baishnaba; Chadag, Vishnumurthy Mohan; Rajendran, Suresh (WorldFish, 2022)
Based on the deliverable -7 of WorldFish under the APART project, the WorldFish Assam team has conducted 12 numbers of small fish nutrition promotion awareness, piloting and demonstration activities in different parts of Assam from 8th March 2022 to 30th March 2022. In total 760 participants including mothers, children, caregivers, community members, ICDS staff, ASHA workers, and community resource persons were given awareness.